2013
DOI: 10.1186/1741-7015-11-119
|View full text |Cite
|
Sign up to set email alerts
|

Developmental heterochrony and the evolution of autistic perception, cognition and behavior

Abstract: BackgroundAutism is usually conceptualized as a disorder or disease that involves fundamentally abnormal neurodevelopment. In the present work, the hypothesis that a suite of core autism-related traits may commonly represent simple delays or non-completion of typical childhood developmental trajectories is evaluated.DiscussionA comprehensive review of the literature indicates that, with regard to the four phenotypes of (1) restricted interests and repetitive behavior, (2) short-range and long-range structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 151 publications
4
27
0
Order By: Relevance
“…Autism spectrum disorder (ASD) refers to a spectrum of early onset neurodevelopmental disorders characterised by poor social reciprocity and communication, combined with repetitive and stereotyped patterns of behaviour, interests and activities (American Psychiatric Association 2000, 2013. Hyper and hyposensitivity to sensory stimulation (e.g., Kern et al 2006;Khalfa et al 2004) as well as atypical sensory processing abilities (e.g., Leekam et al 2007;Simmons et al 2009;Talay-Ongan and Wood 2000) are often reported and have been included in the new diagnostic criteria of ASD in DSM-5 (American Psychiatric Association 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Autism spectrum disorder (ASD) refers to a spectrum of early onset neurodevelopmental disorders characterised by poor social reciprocity and communication, combined with repetitive and stereotyped patterns of behaviour, interests and activities (American Psychiatric Association 2000, 2013. Hyper and hyposensitivity to sensory stimulation (e.g., Kern et al 2006;Khalfa et al 2004) as well as atypical sensory processing abilities (e.g., Leekam et al 2007;Simmons et al 2009;Talay-Ongan and Wood 2000) are often reported and have been included in the new diagnostic criteria of ASD in DSM-5 (American Psychiatric Association 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hyper and hyposensitivity to sensory stimulation (e.g., Kern et al 2006;Khalfa et al 2004) as well as atypical sensory processing abilities (e.g., Leekam et al 2007;Simmons et al 2009;Talay-Ongan and Wood 2000) are often reported and have been included in the new diagnostic criteria of ASD in DSM-5 (American Psychiatric Association 2013). Delayed or deviant speech and language development are also often reported but are no longer incorporated in the diagnostic criteria of the disorder (American Psychiatric Association 2000, 2013.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, among individuals with relatively high-functioning autism, the frequency of insecure attachment is not increased over normative levels [140]. Children with autism certainly tend to impose higher time and energy demands on parents, especially the mother, but the degree to which less extreme and non-pathological autism spectrum phenotypes involve 'overly secure' attachment, which retains elements of early childhood, psychologically simple dependency on the mother [141], remains to be evaluated.…”
Section: (F ) Social Interactions With Kin Early In Life Generate Andmentioning
confidence: 98%